Using SOLPS to confirm the importance of total flux expansion in Super-X divertors. (8th May 2017) - Moulton, D; Harrison, J; Lipschultz, B; Coster, D
Abstract: We show that a central characteristic of Super-X divertors, total flux expansion f R (defined as the ratio of the elementary area normal to the magnetic field at the target to that at the X-point), significantly changes the characteristics of the target plasma for fixed upstream conditions. To isolate the effect of total flux expansion from other effects, we utilise SOLPS-5.0 simulations of an isolated slot divertor leg in a minimally complex, rectangular geometry. The grid is rotated outwards about a fixed X-point in order to perform a scan in which only the total flux expansion increases, by means of a decrease in the target magnetic field at higher major radius. We find that if the SOL remains in the attached, conduction-limited regime throughout the scan, the target electron density scales approximately as f R 2, while the target electron temperature scales approximately as 1 / f R 2, in good agreement with the modified two-point model presented in Petrie et al (2013 Nucl. Fusion 53 113024). If, however, the SOL transitions from the sheath-limited regime to the conduction-limited regime during the scan, the simulated scalings of target electron temperature and density are weaker than predicted by the modified two-point model. The upstream density for transition from sheath- to conduction-limited regimes is found to scale approximately with 1 / f R, in agreement with the modified two-point model. Assessing upstream-density-driven detachment onset, we find that the target electron temperature at which target density rollover occurs (∼0.6 eV) is independent of f R . Given this, the modified two-point model predicts a halving of the upstream (and target) densities at which rollover occurs when f R is doubled, in good agreement with the simulation results.